How to diagnose exercise induced asthma? - Ali, Z. (Asian Journal of Sports Medicine, 2011)
Exercise induced asthma (EIA) is a transient increase in airway resistance after intensive exercise and can be measured as a decline in forced expiratory volume in one second (FEV1). The condition is due to increased training load and inhalation of cold and dry air. Several studies have shown that eucapnic voluntary hyperpnea challenge test (EVH test) is a very sensitive and specific diagnostic method. EVH test develops EIA by hyperventilation of dry gas and the test achieves the same airway obstruction as training in cold and dry air. The test is better than the previously used methacholine challenge test.